JoJo's bizarre adventure. Part 4, Diamond is unbreakable. 8 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2021)
"A multigenerational tale of the heroic Joestar family and their never-ending battle against evil!... Josuke, Koichi, Okuyasu, Jotaro, Rohan and their newfound friends have been searching Morioh for any trace of the serial killer and Stand user Yoshikage Kira. After much effort and many battles against enemy Stands, they've found their prey! But does Kira have the upper hand after all? This is it! Witness the final battle of Yoshikage Kira and Josuke Higashikata, as Deadly Queen and Shining Diamond go head-to-head!"--Provided by publisher.